Image of Berlin in Travel Notes by M. E. Saltykov-Shchedrin “Abroad” - S. S. Zhdanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article deals with the features of the image of the artistic space of Berlin in travel notes of M. E. Saltykov-Shchedrin “Abroad.” The relevance of the study is determined by the need for imagological analysis of topos texts, which reflect the images of “foreign,” in particular, the German element in the framework of Russian culture. The German-marked locus of Berlin in M. E. Saltykov-Shchedrin’s work is realized through a number of motives related to the changed image of the united Germany as a new European empire in the perception of the Russians of the late 19th century, which, in turn, gives the author an opportunity to express his social and critical views on the prospects and trends of Europe. The author considers the motives of the German hidden threat as an aggressive expansion into the outer space, the militarization of Germany with distinguishing the image of a Prussian officer-“a hero” as the central one, spiritual and political unfreedom, order, boredom and at the same time the theatrical appearance of the German existence as the main motives related to the locus of Berlin identified in travel notes by M. E. Saltykov-Shchedrin. It is shown that the basis of the description of the city is the observation of the street life of the German capital. The author of the article comes to the conclusion that in the work by M. E. Saltykov-Shchedrin Berlin is portrayed as non-chronical locus with the characteristics of mortality, which functions similarly to the mechanism on the principle of continuous cyclical movement.